Capacity value analysis of interruptible loads in regional power systems with intermittent renewable energy - Fan, Hengjian; Wang, Hongliang; Xu, Yang; Hu, Jiahua; Zhang, Weiwei; Xiao, Xuanyi (Frontiers in Energy Research, 2022)
The proportion of renewable energy is increasing rapidly to develop low-carbon power systems and the intermittence nature of renewable energy harms the security operation of power systems. The participation of interruptible loads is an effective means to handle the intermittence of renewable energy. However, the capacity value of interruptible loads has not been fully recognized, which results in limited involvement of interruptible loads in power system operations. Hence, it is urgent to analyze the capacity value of interruptible loads. In this paper, a capacity value calculation method of interruptible loads is proposed. A joint optimal operation model of interruptible loads and multiple power sources including thermal power units, hydropower units, and wind turbines is established to realize the application paradigm of power system operations with interruptible loads. Case analysis based on the operation data of the power system in a particular area verifies that the proposed method can effectively recognize the capacity value of interruptible loads and reduce the installed capacity of thermal power units. It thereby lays the theoretical foundation for analyzing the role of interruptible loads in the low-carbon transition of the electric energy industry.